So-called “metal-free” oxygen reduction at graphene nanoribbons is in fact metal driven - Wang, Lu (2015)
The oxygen reduction reaction (ORR) is of key importance in the field of electrochemical energy production. Remarkable catalytic properties of “metal-free” graphene nanoribbons towards the ORR were suggested in previous reports. Herein, we show that the electrocatalytic properties of an undoped supposedly “metal-free” graphene nanoribbon towards the ORR is actually caused by metallic impurities within the graphene nanoribbons.